The Pro-Russian Propaganda Machine in Bulgaria, and the Russian Style Representations of North Macedonia - Vatsov, Dimitar; Dimitrova, Veronika; Donchev, Ljubomir; Valkanov, Valentin; Iakimova, Milena (Identities: Journal for Politics, Gender and Culture, 2023)
The article is based on the large-scale collective research on the topic "Anti-democratic propaganda in Bulgaria", within which an analysis of the national populist and (pro) Russian propaganda in the Bulgarian online media for 2013-2022 was made. This article sets out two main tasks: 1) To outline the global Russian narratives that circulated in the Bulgarian media space online from 2013 to 2022, as well as to outline the means and ways of their dissemination in 2022 - the year of the full-scale war against Ukraine. Part 1 is dedicated to answering these questions. 2) To show how the Russian propaganda package presents the fate of small countries in the global world: how it tries to tempt them to be "sovereign," while, at the same time, not recognizing their capacity to achieve sovereignty. It also shows how Bulgarian speakers denigrate North Macedonia in the same way that Russian propaganda denigrates Ukraine. This is explored in Part 2. Author(s): Dimitar Vatsov, Veronika Dimitrova, Ljubomir Donchev, Valentin Valkanov, Milena Iakimova Title (English): The Pro-Russian Propaganda Machine in Bulgaria, and the Russian Style Representations of North Macedonia Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 68-91 Page Count: 24 Citation (English): Dimitar Vatsov, Veronika Dimitrova, Ljubomir Donchev, Valentin Valkanov, Milena Iakimova, "The Pro-Russian Propaganda Machine in Bulgaria, and the Russian Style Representations of North Macedonia,” Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023): 68-91.